Analyzing determinants of mobile phone usage among dairy farmers in rural Uttar Pradesh - Das, Ajoy; Umashankar Rawat; Sanjeev Kumar Singh; Amit Singh; Vivek Khandait; Harish Chandra Yadav; Naresh Kumar Dahiya (Indian Journal of Dairy Science, 2025)
Farmers can obtain the required information with information and communication technologies (ICTs). Urban and rural communities are exposed to a vast spectrum of ICT tools. However, as people often utilize ICTs more for amusement and leisure, farmers’ effective use of them to get agricultural information is the primary concern. Keeping this in view, the study was designed to examine the factors influencing the usage of livestock-oriented mobile applications among livestock owners of the Mathura district of Uttar Pradesh. The survey comprised a total of 150 respondents after information was gathered from 15 randomly chosen respondents from each village. Data was collected through a pre-designed structured interview schedule. Out of the 18 factors studied, which were further divided into three subcategories. The study revealed that security and privacy among respondents are major concerns before using mobile applications, followed by the application's popularity. The relative advantage of mobile applications over the available sources for livestock information is that the trialability and credibility of information provided by mobile applications were significant factors influencing livestock-oriented mobile application usage among farmers.